2011
DOI: 10.1007/s12011-011-9204-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intensive Physical Activity on Selenium Status

Abstract: Various biomarkers were used to assess selenium (Se) status during 3 months of basic military training in a group of recruits. Samples of whole blood and plasma or serum were taken from a group of conscripts three times: at the beginning (n = 15), in the middle immediately after a severely stressful physical activity (n = 15) and at the end of military training (n = 13). Selenium was determined in diet samples, blood, plasma and plasma protein fractions as selenoprotein P (SelP) and glutathione peroxidase (eGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…However, most of these studies were conducted with elderly volunteers and postmenopausal women and determined the activity of GPx rather than its selenium content, therefore a direct link with our study cannot be made. In the recent study of Pograjc et al, where a similar analytical approach with ours was followed, the basic military training in a group of recruits was unable to affect the levels of TSe, the activity of serum and red blood cell GPx and the relative distribution of serum selenium to GPx-3 and SelP although a trend of lower Se-SelP was observed during training [37].…”
Section: Discussionsupporting
confidence: 52%
“…However, most of these studies were conducted with elderly volunteers and postmenopausal women and determined the activity of GPx rather than its selenium content, therefore a direct link with our study cannot be made. In the recent study of Pograjc et al, where a similar analytical approach with ours was followed, the basic military training in a group of recruits was unable to affect the levels of TSe, the activity of serum and red blood cell GPx and the relative distribution of serum selenium to GPx-3 and SelP although a trend of lower Se-SelP was observed during training [37].…”
Section: Discussionsupporting
confidence: 52%
“…Eastern European countries tended to have lower Se intake than their western counterparts, as indicated by a Polish study [ 25 ], where Se content of the consumed foods was four-times lower than in Spain, which tended to have intakes that exceeded the DRI and RDA [ 26 , 27 , 28 , 29 , 30 ]. Studies in France [ 31 ] and Belgium [ 32 ] reported intakes equivalent to the RDA, while those from Slovenia [ 33 ] and Italy [ 34 , 35 ] found intakes below the RDA.…”
Section: Resultsmentioning
confidence: 99%
“…Selenoprotein P (SeP) is a liver-derived secretory protein, and a significant positive correlation in humans between SeP mRNA expression and insulin resistance was identified using serial analysis of gene expression and DNA chip methods ( 149 ). SeP-deficient mice showed more endurance capacity after training through upregulation of reactive oxygen species and AMPK ( 150 ); however, there was no change in SeP secretion with exercise training in rodents ( 150 ) or humans ( 119 , 151 ), suggesting that inhibition of SeP is an exercise-enhancer rather than an exercise mimicker.…”
Section: Mechanisms By Which Exercise Improves Nafld; a Narrative Revmentioning
confidence: 99%